The Impact of Translation Shift and Method on Translation Accuracy Found at Bilingual History Textbook - Kammer Tuahman Sipayung (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Well-translated bilingual history textbook can be as a well source of language knowledge. The purposes of this research were to figure out the dominant translation shift, method and the impact of dominant shift and method on accuracy translation aspect. The researcher used descriptive qualitative method to figure out the purpose of research. There are two kinds of data in this research: affective and objective data. The affective data are from key-informants in the form of scale. Objective data are from bilingual history textbook choosen randomly sampling in the form of words, phrases, clauses, sentences and text. The findings of this research shows that 1) The dominant translation shift is unit shift 58,33%, structure shift: 30%, class shift: 7,77% and intra-system shift: 3.88%. 2) The dominant translation method is free translation: 57.57%, communicative translation: 19.69%, adaptation translation: 13.63% and semantic translation method: 9.09%. 3) The impact unit shift and free translation method influence the lack accuracy of translation level: 2.38. There are 60% from the bilingual history textbook is lack accuracy of translation.